Conversations with the cannibals the end of the old South Pacific - Krieger, Michael (Ecco Press, 1994)
In this captivating work of nonfiction, Mike Krieger succeeds brilliantly in his "attempt to capture the essence of this dying age, of this disappearing way of life and of the South Pacific's cultures, subcultures, and extraordinary people who all reflect an epoch on the verge of extinction." He takes readers on a wonderful fantasy-expedition from old tramp freighters to dugout canoes, over erupting volcanoes and through remote tropical rainforests to reach his isolated subjects. His openness as a traveller and journalistic skills combine to create a detailed collage of true stories, memorable for their vivid historical and natural contexts. Warmly accommodating a wide variety of island customs and mores, Krieger grounds every fact in vital human experience. He explores two Melanesian and two Polynesian countries where islanders still live according to old traditions. Krieger is the only living person to interview members of different cannibal tribes and to discuss with them the subject of cannibalism. He tells of a tribe whose name in translation means "I Will Kill You," and of a powerful ex-minister whose tyrannical control of a remote island evokes images from Joseph Conrad's Heart of Darkness. In beautifully clear prose, Krieger describes missionaries, cannibals, sorcerers, politicians, and princes - all with wonder and enthusiasm. With painterly discipline and design he chooses moments from his boat rides, jungle treks, and adventures with the people of the South Sea Islands, presenting a picture as intriguing in its particulars as in its overall effect.
Keywords: Alltag, Brauchtum; Ethnology -- Melanesia; Ethnology -- Polynesia; Brauch; Melanesia -- Social life and customs; Polynesia -- Social life and customs; Polynesien; Melanesien